Enhancing Multimodal Interaction and Communicative Competence through Task-Based Language Teaching (TBLT) in Synchronous Computer-Mediated Communication (SCMC) - Belda-Medina, Jose (Education sciences, 2021)
The number of publications on live online teaching and distance learning has significantly increased over the past two years since the outbreak and worldwide spread of the COVID-19 pandemic, but more research is needed on effective methodologies and their impact on the learning process. This research aimed to analyze student interaction and multimodal communication through Task-Based Language Teaching (TBLT) in a Synchronous Computer-Mediated Communication (SCMC) environment. For this purpose, 90 teacher candidates enrolled in the subject Applied Linguistics at a university were randomly assigned in different teams to create collaboratively digital infographics based on different language teaching methods. Then, all the teams explained their projects online and the classmates completed two multimedia activities based on each method. Finally, the participants discussed the self-perceived benefits (relevance, enjoyment, interest) and limitations (connectivity, distraction) of SCMC in language learning. Quantitative and qualitative data were gathered through pre- and post-tests, class observation and online discussion. The statistical data and research findings revealed a positive attitude towards the integration of TBLT in an SCMC environment and a high level of satisfaction with multimodal communication (written, verbal, visual) and student interaction. However, the language teacher candidates complained about the low quality of the digital materials, the use of technology just for substitution, and the lack of peer-to-peer interaction in their live online classes during the pandemic.